NITROGEN ADSORPTION OF URINE WITH ZEOLITE - Utomo, M.Pranjoto; Widjajanti, Endang; Budiasih, Kun Sri (Jurnal Penelitian Saintek, 2010)
Tlte aints of the research v,ere to determine the nitrogen contained in humatt ttrine before and after ipplying zealyte ancl to determine the influence o.f MgO to nitrog'n contained in human urine. The tJetermination of Zeolyte aclsorptio capacity' to nitrogen contained in htrmqn trrine inclLtcled 3 s'teps. Activation ol' nature zeolf ie'nitrogen adsorptiort' Iotal nin"ogen determination Ly Kjeclahl test. Zeolyte activation wqs done by soaking zeollte itio0' 1 14 HCl, HNO: and H2soafor I hour and calcin(ltedJbr t hours at 100"c. The adsorption proses adding y,as clone byaicting inactivated ancl activated zeolyte tuithand without MgO The iptimunt mass of zeolyte was 3 grants. The adsorption capacities oJ' inactivated zeolytes u,ithout And with LttgO adcting were 0.00780994 and 0.0102% pq grdm zeolyte, respectivety. The adsorption Capacities of activated zeoll'te by HCl, HNO: dan H:SO| wiihout Mgo addingw)re 0.00i01%,0.006610.4, and 0a0917?i, per gram:eolil'te. Lhe adsorption capacities of activated zeolyle by HCl, HNO j dan H2SO| v'i* )IgO udding were 0.00839%,0.0i01% dan 0.011% per gram zeoll'te. The activation and lulgO adr)ing increasecl the aclsorption capacitl' oJ' zeolyte to nitrogen contained in httman urine.